Management Administration Smartphone Application as a Strategy to Increase Accreditation Score in Primary Healthcare Facilities - Agus Sugiharto; Boy Subirosa Sabarguna; Ajeng Pramastuty (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2022)
Health facility accreditation has been in great demand in recent years. Mobile applications can serve as a tool for community healthcare center’s (Puskesmas) to assess the value of their accreditation, especially regarding administration and management. In the context of preparation for accreditation, it can be used as a self-assessment tool for elements of management administration. This case-based article focuses on smartphone application development using the input-process-output-outcome scheme as a framework. We developed a checklist and assessment for the management administration component by reviewing Permenkes No. 46 the Year 2015 concerning Puskesmas accreditation. This is the first available mobile application on the Google Play Store, targeting Puskesmas staff to improve the quality of administration and management services based on accreditation criteria. This smartphone application functions as an independent assessment tool for Puskesmas to complete the accreditation criteria as stated in the regulation of the minister of health. About 20 Puskesmas staff showed a very good response and positive. All stated that they were very helpful and satisfied with this application, so they will continue to use and distribute it to other Puskesmas staff.